A abordagem psicossocial sobre a violência de gênero e a violência sexual: uma revisão de literatura - Magalhães, Cátia Luiza Pereira (Kairós: Revista Acadêmica da Prainha, 2021)
This article aims to conduct a literature review on the theoretical framework formulated by Social Psychology about gender violence and sexual violence. Assuming that violence is a multifaceted and multi-causal phenomenon, we identify that these two forms of aggression are characterized by the intense psychosocial damage caused, as well as the invisibility composed by the fear, insecurity and shame that cover the victims, making it so difficult to report them acts as regards seeking appropriate psychosocial support. The survey of this article was conducted from an intense research in the Portal Capes, SciELO and IndexPsi Journals between January and July 2019. The evolution of the researched themes, as well as the importance of the